FULFILLMENT OF CONSTITUIONAL RIGHTS OF BELIEFS PARAMASAN UPPER PRIMARY SCHOOL STUDENTS - yati, Rahmi (JURNAL SOCIUS, 2024)
This classroom action research aims to increase students' interest in learning geography on the subject of the biosphere through cooperative learningstudent teams achievement divisions (STAD) in class XI IPS students at Al-Hidayah Islamic High School.Class research procedures are carried out through a flow process consisting of 4 stages, namely: 1) preparation; 2) planning; 3) implementation; 4) observation and monitoring; 5) reflection; 6) evaluation and revision. Based on the results of the questionnaire, it was found that the percentage increase in the interest score in learning geography in each cycle, the average percentage score of interest in learning geography before the action (initial) was 65.22% and was in the "medium" criteria after cycle I. The average percentage score for interest in learning geography became 67.94% and was in the "medium" criteria after cycle II. The average percentage score for interest in learning geography increased again to 74.40% and was in the "high" criteria. The class average score in the first cycle quiz was 81.5 and experienced an increase in cycle II, namely 82.13. Based on the results of this research data analysis, it can be concluded that the use of cooperative learning is student teams achievement divisions type(STAD) in active learning can increase interest in studying geography, the subject of the biosphere at Al-Hidayah Islamic High School.